Stress Coping Strategies in the Heart: An Integrated View - Michalak, Marek; Agellon, Luis B. (Frontiers in Cardiovascular Medicine, 2018)
The heart is made up of an ordered amalgam of cardiac cell types that work together to coordinate four major processes, namely energy production, electrical conductance, mechanical work, and tissue remodeling. Over the last decade, a large body of information has been amassed regarding how different cardiac cell types respond to cellular stress that affect the functionality of their elaborate intracellular membrane networks, the cellular reticular network. In the context of the heart, the manifestations of stress coping strategies likely differ depending on the coping strategy outcomes of the different cardiac cell types, and thus may underlie the development of distinct cardiac disorders. It is not clear whether all cardiac cell types have similar sensitivity to cellular stress, how specific coping response strategies modify their unique roles, and how their metabolic status is communicated to other cells within the heart. Here we discuss our understanding of the roles of specialized cardiac cells that together make the heart function as an organ with the ability to pump blood continuously and follow a regular rhythm.